Diagnosis of oral cancer: The past and present - G. Sridhar Reddy; K. Eswara Rao; K. Kiran Kumar; P. Chandra Sekhar; K. Lalith Prakash Chandra; B. Venkata Ramana Reddy (Wolters Kluwer Medknow Publications, 2014)
Oral cancer prevalence in Asia-pacific region is at an alarming stage due to the adverse habits and different socio-economic and cultural status of the population. The better understanding of the disease process at the molecular level has altered the approach of the oral cancer towards early diagnosis of the lesion rather than late stages to reduce the morbidity and mortality. A good number of screening techniques has been time tested for the sensitivity and specificity in diagnosing oral cancer in the initial premalignant stages. Surgical biopsy is a gold standard for diagnosis but this needs professional services, which are impractical at times. Alternative screening methods which are noninvasive, easily performed and highly accurate are the norms for any test to accept as an alternative for histopathology. This article focuses on some screening techniques, which are done either as confirmative or adjuvant for histopathology.